2020
DOI: 10.1523/jneurosci.1107-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Corticospinal and Reticulospinal Contributions to Voluntary Control of Elbow Flexor and Extensor Muscles in Humans with Tetraplegia

Abstract: Humans with cervical spinal cord injury (SCI) often recover voluntary control of elbow flexors and, to a much lesser extent, elbow extensor muscles. The neural mechanisms underlying this asymmetrical recovery remain unknown. Anatomical and physiological evidence in animals and humans indicates that corticospinal and reticulospinal pathways differentially control elbow flexor and extensor motoneurons; therefore, it is possible that reorganization in these pathways contributes to the asymmetrical recovery of elb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 86 publications
3
41
0
Order By: Relevance
“…These studies support the idea that after CS tract damage, the muscles with the greatest CM influence show greater weakness, and there may be RM involvement in compensatory (rebalancing) mechanisms for motor alterations (Palmer and Ashby, 1992;Belhaj-Saïf and Cheney, 2000;Zaaimi et al, 2012;Ludolph et al, 2020;Sangari and Perez, 2020). In this way, more recently it has been described in Celsr3| Emx1 mutant mice model, where CST is specifically and fully absent, that axonal projections from RN to the spinal cord are increased and lesions of the RS tract lead to defective forelimb use, with almost no recovery.…”
Section: Segmental Neuronal Circuits Modulated By Cs and Rs Systemssupporting
confidence: 79%
See 1 more Smart Citation
“…These studies support the idea that after CS tract damage, the muscles with the greatest CM influence show greater weakness, and there may be RM involvement in compensatory (rebalancing) mechanisms for motor alterations (Palmer and Ashby, 1992;Belhaj-Saïf and Cheney, 2000;Zaaimi et al, 2012;Ludolph et al, 2020;Sangari and Perez, 2020). In this way, more recently it has been described in Celsr3| Emx1 mutant mice model, where CST is specifically and fully absent, that axonal projections from RN to the spinal cord are increased and lesions of the RS tract lead to defective forelimb use, with almost no recovery.…”
Section: Segmental Neuronal Circuits Modulated By Cs and Rs Systemssupporting
confidence: 79%
“…Ludolph et al (2020) compared strength between elbow extensors (triceps) and flexors (biceps), reporting greater relative weakness in flexors relative to elbow extensors; in addition, they also reported greater relative weakness of extensors vs hand flexors. Similarly, in participants with cervical spinal cord damage (tetraplegia) who received transcranial magnetic stimulation, motor-evoked potentials were smaller in triceps relative to controls, suggesting that there is less CS input to the elbow extensors (Sangari and Perez, 2020). Furthermore, in monkeys with CS tract lesions, Zaaimi et al (2012) reported increased facilitation of motor neurons related to elbow flexors but not in those with connections to extensors.…”
Section: Segmental Neuronal Circuits Modulated By Cs and Rs Systemsmentioning
confidence: 99%
“…For example, a recent study has shown adaptive strategies of motor unit recruitment from the contralesional RST following stroke that prioritize elbow, wrist, and finger flexion synergy over dextrous digit manipulation, which limits functional recovery [112]. Similarly, muscle groups with spared RST input following SCI have been shown to be stronger than those without [113].…”
Section: Plasticity In Spared Descending Systemsmentioning
confidence: 99%
“…Evidence suggests subcortical neural circuits, such as reticulospinal pathways, also contributing to postural adjustments (Prentice and Drew, 2001;Schepens and Drew, 2004;Takakusaki, 2017). Research has shown the reticulospinal inputs being upgraded after spinal cord injury and in ageing as a compensatory mechanism to maintain motor control (Sangari and Perez, 2020;Maitland and Baker, 2021). Although the role of the reticulospinal circuits in modulating corticospinal excitability profile during the APA window remains unknown, it is possible that the reticulospinal circuits influence the control of APAs.…”
Section: Corticospinal Excitability and Apas In The Elderlymentioning
confidence: 99%